KETANGGUHAN SISTEM EKONOMI ISLAM DALAM PEREKONOMIAN DUNIA - Windari Windari (Institut Agama Islam Negeri Padngsidimpuan, 2017)
Goals to be achieved in the activities of this paper to see toughness Islamic economics in the world economy. Due to bad the world economy today which is easy to be swayed by speculators. The study of literature is a major source, regarding various provisions of the studies that have been done before, and is supported by a study published by various agencies in the form of journals and other scientific studies. Islamic economics is a solution for mankind to come out of the crisis and prosper, besides that Islamic economics offers an Islamic economic system built on the foundation of the Islamic faith.